Spontaneous Coronary Artery Dissection – A Case Report - Nahar, Samsun; Begum, Fatema; Momenuzzaman, -; Khan, KN (University Heart Journal, 2018)
Spontaneous coronary artery dissection is a rather rare cause of myocardial infarction, chest pain, and sudden death.There are currently no known direct causes of this condition.Most of the reported dissections have occurred in the left anterior descending coronary artery.Herein, we report the case of a 58-year-old woman who presented at our institution with an acute ST-elevation myocardial infarction secondary to a spontaneous dissection of the right coronary artery. Primary PCIresolved the occlusion of the artery, and the patient was discharged from the hospital on medical therapy. University Heart Journal Vol. 12, No. 2, July 2016; 105-107